Auditing for Performance Evaluation. - Penno, Mark (The Accounting Review, 1990)
Abstract Presents a study which models the internal audit function as a scarce economic resource and the use of that resource for the provision of incentives. Background on the internal audit function; Internal auditing used for performance evaluation; Internal auditing not used for performance evaluation.